(untitled) (International Journal of Food and Nutritional Sciences, 2020)
A social network is a web-based platform that allows users to create profiles, connect with others, share content, and engage in various forms of communication. Social networks have various categories or types according to their purpose of creation. Like LinkedIn, it’s a professional’s social network, and Facebook is a multipurpose social network. Professional networks connect like-minded professionals on the same platform. .On this platform, sharing content, discussion, information, and thoughts is very easy.